2017
DOI: 10.1016/j.immuni.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol Protects Host against Zika Virus Infection and Its Associated Microcephaly in a Mouse Model

Abstract: SUMMARY Zika virus (ZIKV) has become a public health threat due to its global transmission and link to severe congenital disorders. The host immune responses to ZIKV infection have not been fully elucidated, and effective therapeutics are not currently available. Herein, we demonstrated that cholesterol-25-hydroxylase (CH25H) was induced in response to ZIKV infection and that its enzymatic product, 25-hydroxycholesterol (25HC), was a critical mediator of host protection against ZIKV. Synthetic 25HC addition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
301
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 292 publications
(311 citation statements)
references
References 49 publications
6
301
0
4
Order By: Relevance
“…CH25H converts cholesterol to 25-hydroxycholesterol (25HC), a soluble factor that blocks viral entry by inhibiting membrane fusion (Liu et al, 2013). The therapeutic potential for 25HC has been further demonstrated through our recent studies showing that administration to adult non-human primates and mice can reduce viremia and block ZIKV-induced fetal microcephaly when administered during pregnancy (Li et al, 2017). As 25HC is a natural defense protein against several viruses, we tested whether this mechanism could be augmented to alleviate ZIKV-induced cytopathy.…”
Section: Resultsmentioning
confidence: 99%
“…CH25H converts cholesterol to 25-hydroxycholesterol (25HC), a soluble factor that blocks viral entry by inhibiting membrane fusion (Liu et al, 2013). The therapeutic potential for 25HC has been further demonstrated through our recent studies showing that administration to adult non-human primates and mice can reduce viremia and block ZIKV-induced fetal microcephaly when administered during pregnancy (Li et al, 2017). As 25HC is a natural defense protein against several viruses, we tested whether this mechanism could be augmented to alleviate ZIKV-induced cytopathy.…”
Section: Resultsmentioning
confidence: 99%
“…Replicon assay. The ZIKV replicon containing the Renilla luciferase reporter gene was used for mutagenesis analysis (49). The mutants were generated using similar strategies for mutagenesis based on pACNR-GZ01-Intron-IC.…”
Section: Fig 5 Legend (Continued)mentioning
confidence: 99%
“…Here, we first explored the roles of SLA and CS elements with the replicon system of ZIKV (49), in which the structural genes were replaced by the Renilla luciferase reporter gene. Replicon RNAs were transfected into BHK-21 cells, and Renilla luciferase reporter activities were monitored at 6, 24, 48, and 72 h posttransfection (p.t.…”
mentioning
confidence: 99%
“…Interestingly, other hypolipidemic agents targeting sterol-responsive element binding protein (SREBP) activity, such as nordihydroguaiaretic acid and its derivative, tetra-O-methyl nordihydroguaiaretic acid (M 4 N), an anticancer drug in clinical trials, PF-429242, and fatostatin, also reduced ZIKV infection in cultured Vero cells (T. Merino-Ramos, N. Jiménez de Oya, J.-C. Saiz, and M. A. Martín-Acebes, submitted for publication). Along this line, anti-ZIKV activity has also been reported for 25-hydroxycholesterol, which also regulates SREBP activity and is involved in the innate immune response to toll-like receptor ligands and interferon (52). Importantly, 25-hydroxycholesterol inhibited ZIKV infection in vitro (IC 50 , 0.2 M) by blocking viral entry, reduced viremia and conferred protection against ZIKV in mice and rhesus macaques, and reduced tissue damage in human cortical organoids and the embryonic brains of infected mice (52).…”
Section: Host-targeting Antiviralsmentioning
confidence: 91%
“…Along this line, anti-ZIKV activity has also been reported for 25-hydroxycholesterol, which also regulates SREBP activity and is involved in the innate immune response to toll-like receptor ligands and interferon (52). Importantly, 25-hydroxycholesterol inhibited ZIKV infection in vitro (IC 50 , 0.2 M) by blocking viral entry, reduced viremia and conferred protection against ZIKV in mice and rhesus macaques, and reduced tissue damage in human cortical organoids and the embryonic brains of infected mice (52). Finally, an additional study has identified three antimalarial compounds that inhibited ZIKV in Vero cells, namely, quinacrine (EC 50 , 2.3 M), mefloquine (EC 50 , 3.9 M), and GSK369796 (EC 50 , 2.8 M) (53).…”
Section: Host-targeting Antiviralsmentioning
confidence: 91%